ANALISIS DAYA DUKUNG LAHAN POTENSIAL PERMUKIMAN DI KECAMATAN TEMBALANG TAHUN 2021-2041 - Febri Tristiani; Intan Muning Harjanti; Bintang Septiarani (Jurnal Riptek, 2021)
The city is always developing all the time. The development of a city isgenerally synonymous with population growth. The high rate of population growth thatoccurs in a city will be followed by an increase in the rate of settlement growth (Jayadiet al., 2017). Tembalang District which has the main function as an educational areaand is planned as a medium density housing development area equipped with completefacilities and infrastructure is one of the factors causing the increase in population whichresults in an increase in the need for residential land in Tembalang District. This studyaims to determine the availability of potential settlement land along with the carryingcapacity of potential settlement land in Tembalang District in 2021-2041 which wasanalyzed using quantitative descriptive analysis methods and spatial analysis. Based onthe results of the study, it shows that the area of land that has the potential to bedeveloped into a residential area in Tembalang District reaches 814.04 Ha or 19.78%of the total area of Tembalang District., while the population at the end of the analysisyear (2041) in Tembalang District reaches 418,397 inhabitants. After calculating, it wasfound that at the end of the analysis year (2041) the carrying capacity of the potentialland for settlements in Tembalang District was 1 DDP (DDPm = 1). The carryingcapacity of potential residential land of 1 DDP (DDPm = 1) means that the availabilityof residential land in Tembalang District is balanced with the need for residential landin Tembalang District with 6 (six) villages in Tembalang District which are still able toaccommodate the need for residential land including Rowosari, Meteseh, Bulusan,Tembalang, Jangli, and Kramas village.